2017
DOI: 10.1016/j.msea.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanical properties of B2 ordered refractory AlNbTiVZrx (x = 0–1.5) high-entropy alloys

Abstract: Structure and mechanical properties of the AlNbTiVZr x (x = 0; 0.1; 0.25; 0.5; 1; 1.5) refractory high-entropy alloys were investigated after arc melting and annealing at 1200°C for 24 h. The AlNbTiV alloy had a B2 ordered single phase structure. Alloying with Zr resulted in (i) change of the degree of order of the B2 phase; and (ii) precipitation of the Zr 5 Al 3 and C14 Laves ZrAlV phases. The density of the AlNbTiVZr x alloys varied from 5590 kg m −3 for the AlNbTiV alloy to 5870 kg m −3 for the AlNbTiVZr 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
92
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(104 citation statements)
references
References 59 publications
6
92
1
5
Order By: Relevance
“…There are some researches working on the addition of Al [27,28], Mo [29], Ti [30], V [31], or Zr [32], but few of them focus on the elevated-temperature mechanical performance and the overall effect of the constituent elements. To understand the elemental effect on mechanical properties, equiatomic HfMoNbTaTiZr alloy is firstly designed as a base alloy by adding the high modulus refractory element Mo to HfNbTaTiZr.…”
Section: Introductionmentioning
confidence: 99%
“…There are some researches working on the addition of Al [27,28], Mo [29], Ti [30], V [31], or Zr [32], but few of them focus on the elevated-temperature mechanical performance and the overall effect of the constituent elements. To understand the elemental effect on mechanical properties, equiatomic HfMoNbTaTiZr alloy is firstly designed as a base alloy by adding the high modulus refractory element Mo to HfNbTaTiZr.…”
Section: Introductionmentioning
confidence: 99%
“…will be introduced during the preparing process, which will lead to the formation of precipitated phases [4,8,9]. In fact, several recent studies have revealed that in many cases, dual-phase microstructures can be observed in some HEAs [10,11] and the second phase significantly enhances the strength of HEAs by precipitation strengthening [12,13,14,15,16,17]. Therefore, the precipitated phase, caused by introduction of interstitial elements, may benefit the mechanical properties of HEAs in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…HEAs are defined as alloys containing at least five major elements wherein every major element has an atomic fraction between 5% and 35% [9]. Various studies on HEAs, including composition, processing, crystal structure and microstructure, and physical and mechanical properties, have been performed in the past years [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%